Lexic-syntactic expression of intentions of doctor in the professional language (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article analyzes the peculiarities of lexical-syntactic expression of intentions physician during patient interviews. It is revealed that among different types of sentences in the structure of the replica-medical statements dialogical speech activity observed interrogative sentence test character, which contain the answers are alternative content.
Keywords: intention; lexical and syntactic; test; varied; professional